Efektivitas Pelaksanaan Pembelajaran Terbalik (Reciprocal Teaching) Terhadap Motivasi Belajar IPA Murid Kelas V SDN 43 Parasangan Beru Kabupaten Maros - Khaerun Nisa’a Tayibu; Habibi Musa (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
Thus, this study aims to determine the effectiveness of implementing reverse learning (reciprocal teaching) on the science motivation of fifth grade students of SD. This type of research is experimental (true-experimental design). The population in this study were 62 students of Class V SDN 43 Parasangan Beru,. The sample of the study was 58 students where the experimental group was 29 students and the control group was 29 students who were taken using non-probability sampling with a purposive sampling method. The instruments used consisted of teacher and student observation sheets and a science learning motivation questionnaire. Data were analyzed using descriptive statistics and inferential statistics, namely the t test. The results showed that: (i) Implementation of learning using reverse learning (reciprocal teaching) has increased in each meeting, both in terms of learning implementation, student learning activities and student learning motivation. (ii) There are differences in science learning outcomes between before and after being taught using reverse learning (reciprocal teaching), (iii) The use of reverse learning (reciprocal teaching) is effective in increasing science learning motivation for fifth grade.